THE TAIMYR FOLD BELT, ARCTIC SIBERIA: TIMING OF PREFOLD REMAGNETISATION AND REGIONAL TECTONICS - Torsvik T.H.; Andersen T.B. (My University, 2002)
Late Precambrian and Palaeozoic platform sediments from the Central – South Taimyr Peninsula (Arctic Siberia) are all remagnetised. The remagnetisation is prefold and is related to thermal remagnetisation caused by Taimyr Trap magmatism. The remagnetisation age is estimated to 220 – 230 Ma and, hence, is considerably younger than the ca. 251 Ma age for the main body of Siberian Trap flood basalts. The folding that affected the Taimyr region platform sediments also included the Taimyr ''Traps,'' hence, relegating Taimyr deformation to post-Mid Triassic time, and most probably, to a Late Triassic age. This shows that whilst thrusting terminated in the Urals during the Permian, crustal shortening continued in Taimyr, Novaya – Zemlya and the South Barents Sea, well into the Mesozoic.